2013
DOI: 10.1108/jmp-01-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Gender typing in stereotypes and evaluations of actual managers

Abstract: Purpose -The purpose of this paper is to examine gender-related management stereotypes, perceived gender bias and evaluations of actual managers, and to directly compare stereotypes and ratings of actual managers. Design/methodology/approach -Questionnaires were distributed to employees in the bank and insurance sector, and 240 participants rated their actual managers and stereotypes of male and female managers. Findings -Men evaluated the female manager stereotype more positively on communal attributes, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 70 publications
3
16
0
2
Order By: Relevance
“…Apparently, there is no difference between males and females in the construction of positive identity as a leader in the current data set. Although it is surprising, this result is consistent with other studies that report these stereotypes as having decreased over time (Gartzia & Baniandrés, 2015;Li Kusterer et al, 2013;. The current results are also consistent with Grant Thornton's research that shows that 36% of senior managers in Indonesia are women, and the reasons many women advance themselves as leaders are their willingness to make a difference (47%) and to influence others (32%) (Priherdityo, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Apparently, there is no difference between males and females in the construction of positive identity as a leader in the current data set. Although it is surprising, this result is consistent with other studies that report these stereotypes as having decreased over time (Gartzia & Baniandrés, 2015;Li Kusterer et al, 2013;. The current results are also consistent with Grant Thornton's research that shows that 36% of senior managers in Indonesia are women, and the reasons many women advance themselves as leaders are their willingness to make a difference (47%) and to influence others (32%) (Priherdityo, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…In contradiction to Hypothesis 2, we also found that male‐typing of successful managers is stronger for female participants compared to male participants across all conditions. This finding is contrary to research that has found a diminished gender‐typing of managerial roles among women (Booysen & Nkomo, ; Brenner et al ., ; Deal & Stevenson, ; Duehr & Bono, ; Kusterer et al ., ; Schein, ; Sczesny, ), and it suggests that the gender advancements achieved in some countries have not yet been reached in Spain.…”
Section: Resultsmentioning
confidence: 99%
“…A closer analysis revealed that several individual studies (Booysen & Nkomo, ; Brenner, Tomkiewicz & Schein, ; Deal & Stevenson, ; Duehr & Bono, ; Kusterer, Lindholm & Montgomery, ; Schein, ; Sczesny, ) found diminished gender‐typing of managerial roles among women. Cross‐cultural studies (Schein & Mueller, ; Schein et al ., ; Sczesny et al ., ) have shown a similar pattern of gender‐typing for the managerial position among male participants, but a different pattern among female participants.…”
Section: Gender‐typing Of Managerial Rolesmentioning
confidence: 99%
See 2 more Smart Citations